Ekstrak Pollen Kurma (Phoenix dactylifera L) Sebagai Terapi Infertilitas Pada Pria - Devi Rahmadiani (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction Infertility is one of the problems faced by couples who want to have children. Infertility in a year occurs as much as 15% in couples who expect pregnancy. Aim; analyzed that the antioxidant content in DPP can counteract free radicals and prevent oxidative stress. Method; The analysis is carried out with a systematic literature review method by examining, identifying, assessing, and presenting it. Result; found various studies showing that DPP extract has an effect to prevent and treat infertility. Conclusion; that there is a decrease in sperm quality due to increased oxidative stress due to an imbalance of antioxidants and free radicals